2018
DOI: 10.3389/fpsyg.2018.00214
|View full text |Cite
|
Sign up to set email alerts
|

Group Facial Width-to-Height Ratio Predicts Intergroup Negotiation Outcomes

Abstract: Past studies have found that the facial width-to-height ratio (FWHR) is associated with a range of traits and behaviors that are possibly important to dyadic negotiations. However, it is unknown whether the FWHR would have an impact on intergroup negotiations, which happen frequently and often have higher stakes in the real world. To examine this question, in the current study, we randomly assigned 1,337 Chinese business executives into 288 groups and they completed a multi-issue negotiation exercise against e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…This is in keeping with the study of some authors (13,10), where they reported that individuals with higher fWHR were more likely to be judged as untrustworthy, dominant, more powerful, competent and more likely to take risks to get money and other resources (13,10). The findings of the current study, although weak and insignificant, agrees with the previous studies that reported individuals with high values of fWHR as successful, powerful and putatively rich (10,14) and achieve better negotiation outcomes in business (15). It is logical to also argue that such individuals with lower fWHR are more likely to be duped in the business since they may be less powerful, less dominant, and incompetent when they indulge in business.…”
Section: Discussionsupporting
confidence: 92%
“…This is in keeping with the study of some authors (13,10), where they reported that individuals with higher fWHR were more likely to be judged as untrustworthy, dominant, more powerful, competent and more likely to take risks to get money and other resources (13,10). The findings of the current study, although weak and insignificant, agrees with the previous studies that reported individuals with high values of fWHR as successful, powerful and putatively rich (10,14) and achieve better negotiation outcomes in business (15). It is logical to also argue that such individuals with lower fWHR are more likely to be duped in the business since they may be less powerful, less dominant, and incompetent when they indulge in business.…”
Section: Discussionsupporting
confidence: 92%
“…Stronger evidence supports the notion that the FWHR may have been a sexually selected trait in men, which signals formidability to other male rivals [ 29 ]. Similarly, men with relatively larger FWHRs have the ability to outcompete men with lower FWHRs in sports [ 30 , 31 ], business [ 32 , 33 ], physical fights [ 9 ] and warfare [ 26 ], all of which may lead to status, wealth and obtaining other reproductively relevant resources and hence greater mating opportunities.…”
Section: Tracking Sexual Dimorphism Of Facial Width-to-height Ratio A...mentioning
confidence: 99%
“…Instead of using eyebrows, facial height is sometimes taken from the eyelids (Lefevre et al, 2014; Stirrat & Perrett, 2010; Yang et al, 2018), but according to our results, the nasion may be an even better choice (Kramer, 2017; Weston et al, 2007) because its vertical position should be quite independent from muscular activations around the eyes, including their clenching in connection with anger. In fact, when using the nasion instead of the eyebrows to determine facial height, we did not find any significant influence of state-emotionality on fWHR, not even in the photo-edited faces.…”
Section: Discussionmentioning
confidence: 89%